Pengaruh Penggunaan Effective Microorganism 4 (EM4) Pada Budidaya Jamur Merang (Volvariella volvaceae) Menggunakan Media Tandan Kosong Kelapa Sawit. - Andriyanto Andriyanto; Retni S Budiarti; Agus Subagyo (Jurnal Biologi Universitas Andalas, 2019)
Indonesia is the biggest producer of palm oil in the world. Palm oil empty fruit bunches is the biggest waste generated by the palm oil processing industry. However, utilization of the palm oil empty bunches has been not optimal. The palm oil empty fruit bunches have potential to be developed into a medium for growing mushroom because it has a high cellulose content. However, the high content of cellulose and lignin in palm oil empty fruit bunches is difficult to decompose into organic material that need for mushroom growth. The composting processes of empty fruit bunches can be increased by using Effective Microorganism (EM4). This study aims to understanding the role of Effective Microorganism 4 (EM4) on Volvariella volvaceae cultivation processes that used Empty Fruit Bunches compost. This research was conducted by composted the empty fruit bunch with different concentration of EM-4 there are 0%, 10%, 15%, 20% and 25%. Parameters observed were number of mushrooms, weight of mushrooms and C / N ratio of compost. The results showed that EM-4 had reduce C/N ratio of empty bunch palm oil compost, C/N ratio was not affected mushroom production and EM4 was affected mushroom production, the highest production reached by concentration of 15% that had not significant with concentration of 5%, 10% and 20%. At concentration of 25% mushroom production was decreased. It is probably there are several mechanisms by EM4 microorganisms containing that affected mushrooms production.